The First Edition of Manuscript Syair Qasidah Burdah - Bodi, Idham (PUSAKA, 2015)
Qashidah Burdah is written by Sharafuddin Muhammad Abu Abdillah bin Zaid Al-Bushiri (610-694 H/1213-1294 M). This work is very popular in the literary treasures of Islam. It contained the poems of praise to the Prophet Muhammad, namelya moral, spiritual values, and fighting spirit. Al Bushiri Berber descent who was born in Dallas, is from Morocco and raised in Egypt. Since he was child, Al Bushiri had learned the science and Arabic literature. His surplus is to write poems that skill exceeds the poets of his time. Until now Burdahis still often read in the various regions in Indonesia, especially on the anniversary of the Prophet's Birthday. This work has also been translated into many languages.O​ne of them is Indonesian, and also several regional languages ​​in Indonesia.